Exploiting Social Media for Active Pharmacovigilance: The PVClinical Social Media Workspace - Kakalou, Christine; Dimitsaki, Stella; Dimitriadis, Vlasios K; Natsiavas, Pantelis (Studies in health technology and informatics, 2022)
The value of social media data for Adverse Drug Reaction (ADR) monitoring is actively investigated. While social media provide a vast amount of data, these data are hard to analyse due to their unstructured nature and lack of credibility. Despite these challenges, social media have been identified as a potentially useful data source, potentially able to "strengthen" the evidence for new ADRs. To this end, PVClinical project aims to build a platform facilitating the investigation of multiple heterogeneous data sources, including social media, to support pharmacovigilance (PV) processes, both in the clinical environment and beyond. In this study, we present the PVClinical Twitter workspace, also highlighting the rationale behind the main design choices, while also discussing the respective challenges.